Systemic lupus erythematosus - Lahita, Robert G. (Robert George), 1945- (Academic Press, 2021)
Systemic lupus erythematosus (SLE), commonly called lupus, is a chronic autoimmune disorder that can affect virtually any organ of the body. In lupus, the body's immune system, which normally functions to protect against foreign invaders, becomes hyperactive, forming antibodies that attack normal tissues and organs, including the skin, joints, kidneys, brain, heart, lungs, and blood. Lupus is characterized by periods of illness, called flares, and periods of wellness or remission. Because its symptoms come and go and mimic those of other diseases, lupus is difficult to diagnose. There is no single laboratory test that can definitively prove that a person has the complex illness. To date, lupus has no known cause or cure. Early detection and treatment are the key to a better health outcome and can usually lessen the progression and severity of the disease. Anti-inflammatory drugs, antimalarials, and steroids (such as cortisone and others) are often used to treat lupus. Cytotoxic chemotherapies, like those used in the treatment of cancer, are also used to suppress the immune system in lupus patients. A new edition of this established and well-regarded reference combines basic science with clinical science to provide a translational medicine model. Systemic Lupus Erythematosus, Sixth Edition, is a useful reference for specialists in the diagnosis and management of patients with SLE, a tool for measurement of clinical activity for pharmaceutical development and basic research of the disease, and a reference work for hospital libraries.